Promising practice for maintaining identities in First Nation adoption - Carriere, Jeannine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
The purpose of this article is to explore the importance of identity in First Nation adoption. It is adapted from a PhD study completed by the author in 2005. The objectives of this study were: (1) describe how connectedness relates to health for First Nation adoptees, and (2) explore legislative, policy and program implications in the adoption of First Nation children. The ﬁndings suggest that, for First Nation adoptees, there is a causal relationship between connection to birth family, community and ancestral knowledge, adoption and health. The major ﬁnding is that loss of identity may contribute to impaired physical, spiritual, mental and emotional health for First Nation adoptees. This article provides suggestions on how identity can be preserved in First Nation adoption through programs, policies and practice.